Експансія Parthenocissus quinquefolia (L.) Planch. у насадження Криворіжжя - Korshikov, I.I.; Bondarenko, I.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to analyse of the spontaneous spread of Parthenocissus quinquefolia (L.) Planch. in the Krivyi Rih park plantations and it impact on the condition of the woody plantations. Material and methods. We used traditional dendrological, biometric and statistical methods in research. Results. It has been established that P. quinquefolia is occurred in the launched parks, where it creates vertical and terrestrial forms. Projective liana covering in the biggest investigated park on the area 2.3 ha is 100 %, on the area 6,0 ha – from 5 to 95 %. As a support liana uses ten basic species of the woody plants in this park and covers to 4/5 of their krone. Species of the plants, on which P. quinquefolia grows and evolves are identified. Conclusions. P. quinquefolia maximally covers 91.7 % of teunk of Picea abies (L.) H. Karst trees and minimally 38.3 % on height Populus pyramidalis Salisb. plants in the neglected park. Desiccation of the branches was observed from 1.3 % in Fraxinus excelsior L. to 78.3 % in P. abies. On the tree trunks it was counted from 4.2 liana vertical offshoots in Robinia pseudoacacia L. to 25.6 in Betula pendula Roth. Liana spreads around the trees on the land in radius to 9 m. It spreads into park plantations that are removed on 500–700 m. In the separate plantations P. quinquefolia demonstrate itself type of transformer.